Dampak Karakteristik Pemasaran Syariah terhadap Kepuasan Nasabah Produk Deposito Mudharabah di Bank Mitra Syariah Gresik Kantor Kas Menganti - Nia Febrianti; Farid Ardyansyah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research conducted by this researcher is something that can be used to understand the importance of applying the characteristics of Islamic marketing and the importance of customer satisfaction for a bank. This study aims to determine how the impact of sharia marketing characteristics on customer satisfaction in deposit products made by Bank Mitra Syariah Gresik. This field research used a qualitative approach, using primary data and secondary data. Then retrieve data sourced from interviews with banks and customers and supporting data, namely through journals and the internet as a reference for relevant researchers. The data testing method used by researchers is data triangulation. The type of triangulation used in this research is source triangulation, namely by checking the data obtained through 3 (three) sources. The results of this study indicate that the characteristics of sharia marketing that have been carried out by Bank Mitra Syariah employees have had a good impact on customers. In marketing deposit products, Bank Mitra Syariah employees have implemented the characteristics of sharia marketing. The characteristics of sharia marketing are theistic (rabbaniyah), ethical (akhlaqiyyah), realistic (al-insaniyyah), and humanistic (al-waqi'iyah). Customers are satisfied with the characteristics of sharia marketing implemented by employees of Bank Mitra Syariah Gresik. Keywords: Islamic Marketing Characteristics; Customer Satisfaction; Deposit Product